WORKSHOP OF MICROCONTROLLER AND ROBOTIC” TO 5 SENIOR HIGH SCHOOLS IN BANDAR LAMPUNG - hilda yunita; KHOZAINUZ ZUHRI (Universitas Nahdlatul Ulama Lampung, 2020)
In line with technological development, dream house concept was integrated with modern technology to assist human stay comfortable and practically didi activity inside. Because of will to praticipate in creating apply technological development community and bearing Indonesian young inventor since they were junior and senior high school student, team consist of lecturers of UMITRA Lampung held a workshop or intensive practice with theme “Workshop about microcontroller and robotic”. This community dedication community in basic practice activity about microcontroller and robot form have been realized in robotica practice room of Fakultas Komputer Universitas Mitra Indonesia. This program was purposed to 5 senior high schhol in Bandar Lampung.